The Relationship Spousal Support and Medication Adherence among Coronary Heart Disease Patients - Prasjodi Fajar Hutama Sudarsono; Dian Hudiyawati (Indonesian Journal of Global Health Research, 2026)
Coronary heart disease (CHD) is one of the leading causes of mortality worldwide, including in Indonesia. Medication adherence is a crucial factor in preventing complications and improving quality of life among patients. This study aimed to examine the relationship between spousal support and medication adherence among patients with coronary heart disease. A quantitative study with a cross sectional design using a systematic sampling technique was conducted among 159 CHD patients attending the cardiac outpatient clinic at Dr. Moewardi General Hospital, Surakarta. Data were collected using a spousal support questionnaire and the Morisky Medication Adherence Scale MMAS 8 and analysed using the Spearman Rho test with a 95 percent confidence level. The results showed a significant positive relationship between spousal support and medication adherence with p value 0.001 and correlation coefficient r 0.482. Patients who received high spousal support demonstrated better medication adherence compared to those with low support. Spousal support plays an important role in improving medication adherence among patients with CHD and should be considered in long term disease management strategies.